Pengaruh Desain Produk, Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Pada Batik Tulis Canteng Koneng Sumenep (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract The purpose of this study was to determine the effect of product design, product quality and price on purchasing decisions on Canteng Koneng Sumenep batik.The population of this research is consumer consumers who come to Padepokan Batik Tulis Canteng Koneng in 2021. The sample used is 83 samples that meet the criteria in the research subject. The analytical method used is multiple regression equation, normality test, classical assumption test, descriptive statistical analysis and hypothesis testing.The results showed that product design, product quality and price influenced purchasing decisions on Canteng Koneng Sumenep batik. Keywords: Product Design, Product Quality, Price and Purchase Decision